PERANAN PENGAWASAN DAN PENYELAMATAN KREDIT DALAM MEMINIMALKAN KEMUNGKINAN GAGAL BAYAR PADA PENYELESAIAN KREDIT MODAL KERJA (STUDI KASUS PADA PT BPR EKA BUMI ARTHA METRO) - Herni Kurniawati; Nedi Hendri; Elmira Febri Darmayanti (Universitas Muhammadiyah Metro, 2020)
The purpose of this study was to find out how the role of supervision and credit rescue in minimizing the possibility of default on the completion of working capital loans at PT BPR Eka Bumi Artha Metro. The method in this studyis descriptive qualitative. Data collection techniques used are observation, interview, documentation. Theanalytical tool used is descriptive method. The results of this study indicate that the credit control section hasperformed its role to the maximum extent possible, but the risk of external factors cannot be avoided.Whereas the credit rescue department has carried out its role to the maximum extent possible in returning nonperforming loans by way of negotiating settlement or by selling voluntary collateral assets, thereby reducing therate of increase in NPLs so that credit quality is maintained. This can be seen from the good credit quality in 2013and 2014, namely the NPL is 1% below the maximum limit of 5% in accordance with Bank Indonesia regulations.Furthermore in 2015NPL increased by 5% from the previous year, which is 9% which means that it is above 4%of the maximum credit limit. And in 2016 and 2017 NPL decreased by 1% from the previous year, which is to 8%,which means above 3% the maximum credit limit. The credit supervision and rescue team has sought to reduce therate of increase in NPLs so that credit quality is maintained. This has been provenbecause in 2016 and 2017the quality of NPLs decreased 1% from the previous year which experienced a 5% increase in NPLs.